Design of a Compact Circular Microstrip Patch Antenna for 5G Applications - Djouimaa, Awatef; Bencherif, Karima (Engineering, Technology & Applied Science Research, 2024)
This paper presents the design and analysis of a compact circular microstrip patch antenna for 5G millimeter wave technology applications. The dimensions of the proposed patch are 5.959 mm × 5.959 mm × 1.400 mm. The antenna exhibits a resonant frequency of 28 GHz, a return loss of -45 dB, a bandwidth of 1.7638 GHz, and a gain of 0.1573. In order to meet the requirements of 5G applications at 28 GHz, a compact, high-gain, and large bandwidth antenna is necessary. The principal objective of this study is to enhance the performance of the antenna parameters, thereby achieving an optimal balance between size, gain, and bandwidth. A notable improvement in bandwidth and gain is achieved. The design, analysis, and optimization processes were conducted using the High Frequency Surface Structure (HFSS) software, which employs the Finite Element Method (FEM) numerical method.